MEMÓRIA E FORMATO NAS ADAPTAÇÕES PARA TELEVISÃO DE GABRIELA, CRAVO E CANELA: DO ERUDITO AO POPULAR MIDIÁTICO - Gedy Brum Weis da Silva (2023)
Contemporary cultural products are marked by the constant presence of retakes of texts belonging to past social contexts and media that narrate their stories in different languages. This research discusses the reuse of literary works for television audiovisual, and aims to analyze the relationship between memory and updating in adaptation, in its thematic and generic aspects, observing the intertextual and intermedial elements present in the transposition. For this purpose, a case study is made of the adaptations of the novel Gabriela, cravo e canela, (1958), by Jorge Amado, to the novel Gabriela (1975), by Walter George Durst, and the novel of the same name (2012), by Walcyr Carrasco. Firstly, the transposition of Amadiana's work to television products is analyzed, discussing adaptation, mediation and memory, focusing on the logic of production in the industrial format and new supports, which imply changes in the literary text, crossed by memory - as reminiscences and experiences. Secondly, the difference in authorship between the two works is discussed, and the changes resulting from adjustments to the conventions of the genre are examined, given that the soap operas have melodramatic matrices and roots in the feuilleton. Finally, an analysis of the narrative categories of time and space is undertaken, mapping how the female characters use spatialities from the perspective of the lived, the inhabited and the practiced. Among the conclusions reached, the following points stand out: it should be noted that, reminiscent of the themes of Amadiana's literary work, the sociocultural context influences updates in the composition of the novels such as the deletions of characters, the addition of themes and other operations of the composition, the industrial format brings changes in the arc of the narrative and the anticipation of the love story of the protagonist characters, the effect of incarnation and the different aesthetic treatment between the works point to the relevance of the materiality of the media. It appears that the generic updates, present in the conception of the television narrative, take up aspects of the serial and melodrama themes, which highlight the presence of these cultural matrices in the mass works. Finally, it appears that soap operas do not expand the spaces for female action in cultural products.